Diagnosis of Hodgkin’s Lymphoma Using Endobronchial Ultrasound-Guided Transbronchial Needle - Abdullah Fahad Almsareer; Ahmed Zaid Alkhathlan; Doaa Ali AlGhamdi; Khalid Alokla (Case Reports in Medicine)
Endobronchial ultrasound-guided transbronchial biopsy has emerged as an excellent tool in diagnosing lung cancer. However, its use to diagnose lymphoma has been questioned, since the gold standard for diagnosing lymphomas is an excisional biopsy of involved lymph nodes. However, the procedure is sometimes risky or difficult. Recent studies have been showing great results using endobronchial ultrasound-guided transbronchial needle aspiration when accompanied by immunohistochemistry and cytology. Here, we present a case of Hodgkin’s lymphoma patient that was accurately diagnosed using endobronchial ultrasound-guided transbronchial needle aspiration.